Biopsychosocial strategy to avoid subsequent pregnancy in adolescence - Rogelio Bárbaro González Pérez; Mallelin Rodríguez Mateo; José Alejandro Concepción Pacheco; Gladys Alejandra Rojas Sánchez; Juan Carlos Mirabal Requena; Belkis Alvarez Escobar (Gaceta Médica Espirituana)
Background: Subsequent adolescent pregnancy is a social problem, also one of the main biopsychosocial risk factors.